The Journey of Self-Discovery: Narrating The Important of Learning In Alternative School Context - Purwaningsih, Nining; Rosmilawati, Ila; Maysara, Siska Resti; Mutaqin, Moh. Fikri Tanzil (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2026)
This study explores how learners in an Indonesian Community Learning Center reconstruct the meaning of education after experiencing educational disruption. Grounded in transformative learning theory (Mezirow) and identity status theory (Marcia), the study employs a qualitative narrative approach to examine the experiences of ten learners at PKBM Darul Ibtida in Serang, Banten. Data were collected through semi-structured narrative interviews and analyzed using thematic analysis. The findings identify five major themes shaping learners’ journeys: disorienting experiences as the starting point of self-discovery; reframing education from a lost pathway into a meaningful alternative; rebuilding confidence and learner identity; developing autonomy in managing learning and life responsibilities; and expanding social awareness and responsibility. These narratives illustrate how learners reinterpret educational disruption and gradually reconstruct their agency and aspirations. The study highlights alternative education as a space for transformative meaning-making and identity reconstruction. Keywords: alternative education, self-discovery, transformative learning